Evaluating TOEIC Instruction through the CIPP Model: Insights from an Indonesian Aviation Academy - Hendra Sudarso; Safitri Era Globalisasi; Dimas Hari Cahyo; Yasyfa’ Kawakibi; Haris Dibdyaningsih (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
English proficiency is essential for safe pilot-air traffic controller communication in aviation operations. While many Indonesian flight academies adopt TOEIC as an institutional benchmark for English certification, questions remain about its effectiveness in measuring the communicative competence required for operational aviation contexts. This qualitative study evaluated TOEIC instruction at an Indonesian Flight Academy using the CIPP (Context, Input, Process, Product) evaluation model. Data revealed a significant gap between strong institutional policy endorsement of TOEIC and actual classroom practice. Although institutional frameworks mandated TOEIC certification, curriculum implementation remained insufficiently aligned with ICAO language proficiency standards, instructors lacked specialized aviation English training, and teaching focused predominantly on test preparation rather than authentic communication scenarios. Notably, while cadets achieved respectable TOEIC scores (550–780), their operational communicative readiness during simulated aviation tasks remained limited. The study recommends curriculum realignment linking TOEIC objectives with ICAO descriptors, mandatory ESP professional development for instructors, and integration of simulation-based communicative tasks. Learner self-efficacy emerged as a crucial psychological factor mediating the transfer of language learning to real communication. This evaluation contributes to ESP pedagogy and aviation English policy by demonstrating how institutional, pedagogical, and psychological dimensions interact to shape language instruction effectiveness in professional, safety-critical contexts.